2009
DOI: 10.1007/s00428-009-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Extraconal orbital tumors in children—a spectrum

Abstract: Orbital masses in children are uncommon but extremely challenging problems for clinicians and pathologists due to their critical location and availability of limited diagnostic material. We analyzed 47 specimens comprising biopsies, excision specimens, and FNAC of extraconal pediatric orbital masses (excluding retinoblastoma) accessioned in the pathology department over 5 years in a tertiary referral cancer center. Immunohistochemistry (IHC-74%) and molecular methods (one case) were done where necessary. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…2,5,9 The frequency and distribution of tumor diagnosis and their association with age is in accordance with past studies that too have demonstrated a relatively higher frequency of vascular and lacrimal gland tumors among operable orbital neoplasms. 3,5,[9][10][11][12][13] Proptosis is the commonest presentation reported in orbital tumors, and in our series the mean proptosis is quite similar to previous data. 3,14,15 In effect, our series is a universally representative sample of orbital tumors.…”
Section: Discussionsupporting
confidence: 90%
“…2,5,9 The frequency and distribution of tumor diagnosis and their association with age is in accordance with past studies that too have demonstrated a relatively higher frequency of vascular and lacrimal gland tumors among operable orbital neoplasms. 3,5,[9][10][11][12][13] Proptosis is the commonest presentation reported in orbital tumors, and in our series the mean proptosis is quite similar to previous data. 3,14,15 In effect, our series is a universally representative sample of orbital tumors.…”
Section: Discussionsupporting
confidence: 90%
“…Por su localización orbitaria, el diagnóstico de inicio es clínico. Son necesarias las técnicas de imagen (TAC o RMN) para la confirmación de la presencia de una masa orbitaria, y para valorar localización y extensión 5 .…”
Section: Discussionunclassified
“…Currently, there is not enough evidence to suggest routine use of PET/CT in orbital RMS at present. [ 10 11 ]…”
Section: Rhabdomyosarcoma Of Orbitmentioning
confidence: 99%